Influence of Musical Experience of Blind and Visually Impaired Young Persons on Performance in Selected Auditory Tasks on Performance in Selected Auditory Tasks - BOGUSZ-WITCZAK, Edyta; SKRODZKA, Ewa; TURKOWSKA, Hanna (Archives of Acoustics, 2015)
The impact of musical experience on results concerning sound perception in selected auditory tasks, such as pitch discrimination, pitch-timbre categorization and pitch memorization for blind and visually impaired children and teenagers is discussed. Subjects were divided into three groups: of those with no experience of music, with small musical experience and with substantial musical experience. The blind and visually impaired subjects were investigated, while sighted persons formed reference groups. To date no study has described impact of musical experience on results of such experiments for blind and visually impaired children and teenagers. Our results suggest that blind persons with musical experience may be more sensitive to frequency differences and differences in timbre between two signals as well as may have better short-term auditory memory than blind people with no musical experience. Musical experience of visually impaired persons does not necessary lead to better performance in all conducted auditory tasks.